Dietary niacin supplementation improves meat quality, muscle fiber type, and mitochondrial function in heat-stressed Taihe black-bone silky fowls - Mei, Wenliang; Zhang, Wenyan; Hu, Ziyu; Qu, Mingren; Wan, Gen; Guo, Xiaoquan; Chen, Chuanbin; Xu, Lanjiao (Frontiers in Veterinary Science, 2024)
BackgroundA recent study has shown that niacin supplementation induces the conversion of type II to type I muscle fibres, thereby promoting a phenotypic shift in oxidative metabolism in porcine skeletal muscle. These effects may be mediated by modulation of the AMPK1/SIRT1 pathway, which activates peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α), a key regulator of fibre conversion, thereby promoting skeletal muscle mitochondrial biogenesis and myofibre conversion. In this study, we explored how niacin (NA) supplementation impacts the quality of meat and the characteristics of muscle fibers in Taihe Black-bone Silky Fowls (TBsf) exposed to heat conditions.MethodsChickens were rationally assigned to five different treatment groups with five replicates of six chickens each: thermophilic (TN), heat stress (HS) and HS + NA (HN) groups, with the HN group being supplemented with 200, 400 and 800 mg/kg (HS + NA0.02, HS + NA0.04 and HS + NA0.08) NA in the premix, respectively.ResultsThe results of the experiment showed that addition of 800 mg/kg NA to the diet significantly improved TBsf muscle tenderness compared to HS. Dietary enrichment with 200-800 mg/kg NA significantly increased total antioxidant capacity, superoxide dismutase, and glutathione peroxidase activities, while significantly decreasing malondialdehyde compared to HS. Incorporation of 200-800 mg/kg NA into the diet significantly reduced lactate dehydrogenase activity and myosin heavy chain (MyHC-IIB) gene expression. Furthermore, adding 800 mg/kg NA can significantly enhance the mRNA expression of mitochondrial transcription factors (TFAM and TFB1M) in TBsf skeletal muscle. Adding 400 and 800 mg/kg of NA significantly increased the mRNA expression of AMP-activated protein kinase 1 (AMPK1), PGC-1α, cytochrome c oxidase (Cytc), and nuclear respiratory factor (NRF-1) in the skeletal muscle of TBsf. Supplementing NA at 200-400 mg/kg significantly increased the expression of Sirtuin 1 (SIRT1) mRNA in TBsf skeletal muscle.ConclusionThe experimental results showed that the addition of NA to the diet reduced the shear force of TBsf muscle under heat exposure conditions. It increased the proportion of type I muscle fibres by increasing the antioxidant capacity of the muscle and by promoting mitochondr fibreial biogenesis. Considering the results of this study, it is recommended that TBsf be supplemented with 400-800 mg/kg of NA in the diet to reduce the adverse effects of heat stress on meat quality.